THE LINGUISTIC ANALYSIS OF ETHNO-CULTURAL FEATURES IN EUPHEMISMS - O. Nurjonov (International Journal of Literature and Language Studies, 2026)
Resume. The article investigates cultural features of ephemisms in Uzbek dialects and analyzes the example with other languages. It mainly studies the traditions and customs associated with linguistic culture.